Alpha-adrenergic receptor agonists in terms of modern views on glaucoma monitoring and treatment - V.P. Erichev; S.Yu. Petrov; A.V. Volzhanin; D.M. Safonova; T.V. Yaremenko; S.A. Kazaryan (РМЖ "Клиническая офтальмология")
The article reviews historical aspects of direct and indirect (by reducing intraocular pressure (IOP)) neuroprotective effect of brimonidine in terms of modern views on glaucoma monitoring and treatment. Brimonidine, a selective alpha-adrenergic receptor agonist, is the first-line treatment choice for glaucoma. This agent reduces IOP by decreasing aqueous humor production and improving uveoscleral outflow. The result is the achievement of target IOP. Brimonidine prevents ganglionic cell death in glaucomatous optic neuropathy. Several in vitro and in vivo studies describe the mechanism of preventing mitochondrial dysfunction and excitotoxic retinal cell damage in ischemia. Brimonidine affects NMDA receptors, inhibits proapoptotic protein expression, activates neurotrophic processes, and normalizes oxidative phosphorylation thus preventing mitochondrial dysfunction.  According to the modern concept, the aim of glaucoma treatment is to avoid vision loss by preventing ganglionic cell death. Therefore, lifelong visual field monitoring and neuroprotective therapy are required. Brimonidine provides target IOP and prevents retinal cell death thus preserving vision in glaucoma.  Keywords: glaucoma, intraocular pressure, neuroprotection, visual field, monitoring, brimonidine, Luxfen.  For citation: Erichev V.P., Petrov S.Yu., Volzhanin A.V. et al. Alpha-adrenergic receptor agonists in terms of modern views on glaucoma monitoring and treatment. Russian Journal of Clinical Ophthalmology. 2019;19(2):87–91.  About the authors: 1Valery P. Erichev — MD, PhD, Professor, Head of Glaucoma Department, ORCID iD 0000-0001-6842-7164; 1Sergey Yu. Petrov — MD, PhD, Leading Research Associate of Glaucoma Department, ORCID iD 0000-0001-6922-0464; 1Andrey V. Volzhanin — postgraduate, ORCID iD 0000-0002-1421-8882; 1Darya M. Safonova — MD, PhD, Junior Research Associate of Modern Treatmen in Ophthalmology, ORCID iD 0000-0002-5082-1494; 2Tamara V. Yaremenko — postgraduate, ORCID iD 0000-0002-3094-1958; 3Serzh A. Kazaryan — resident, ORCID iD 0000-0003-2258-2964. 1Reseach Institute of Eye Diseases. 11A Rossolimo str., Moscow, 119021, Russian Federation. 2Sechenov University. 8 Trubeckaya Str., Moscow, 119146, Russian Federation. 3Mkhitar Heratsi Yerevan State Medical University. 2 Koryuna str., Erevan, 0025, Republic of Armenia. Contact information: Andrey V. Volzhanin, e-mail: avolzhanin@mail.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 11.04.2019.